1998
DOI: 10.2307/259290
|View full text |Cite
|
Sign up to set email alerts
|

Initial Trust Formation in New Organizational Relationships

Abstract: ABSTRACT:Trust is a key enabler of cooperative human actions. Three main deficiencies about our current knowledge of trust are addressed by this paper. First, due to widely divergent conceptual definitions of trust, the literature on trust is in a state of construct confusion. Second, too little is understood about how trust forms and on what trust is based. Third, little has been discussed about the role of emotion in trust formation.To address the first deficiency, this paper develops a typology of trust. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
1,267
3
35

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,266 publications
(1,339 citation statements)
references
References 21 publications
34
1,267
3
35
Order By: Relevance
“…Even though trust is considered to be the default when there is no reason for doubt (e.g., Berg, Dickhaut, & McCabe, 1995;McKnight, Cummings, & Chervany, 1998;cf., Gilbert, 1991), trust is quite easily destroyed and replaced by distrust instead (cf., Cook, Hardin, & Levi, 2005): Suspicion is readily evoked by subtle cues of unreliability, by one single questionable action, or by an isolated instance of betrayal (cf., Marchand & Vonk, 2005). In contrast, for perceiving someone as truly and completely trustworthy or in order to regain a previously damaged reputation of trustworthiness, it takes substantially more evidence of honesty and reliability (cf., Gidron, Koehler, & Tversky, 1993).…”
mentioning
confidence: 99%
“…Even though trust is considered to be the default when there is no reason for doubt (e.g., Berg, Dickhaut, & McCabe, 1995;McKnight, Cummings, & Chervany, 1998;cf., Gilbert, 1991), trust is quite easily destroyed and replaced by distrust instead (cf., Cook, Hardin, & Levi, 2005): Suspicion is readily evoked by subtle cues of unreliability, by one single questionable action, or by an isolated instance of betrayal (cf., Marchand & Vonk, 2005). In contrast, for perceiving someone as truly and completely trustworthy or in order to regain a previously damaged reputation of trustworthiness, it takes substantially more evidence of honesty and reliability (cf., Gidron, Koehler, & Tversky, 1993).…”
mentioning
confidence: 99%
“…McKnight et al [33], McKnight et al [34], and Koufaris and Hampton-Sosa [28] pointed out that when a new innovative service such as mobile banking is introduced, there is no prior experience to fall back on. The experience or knowledge-based trust that normally develops through iterative interactions may not exist.…”
Section: Trust In Mobile Banking Technologymentioning
confidence: 99%
“…McKnight et al [34], showed that a person initial trust mobile banking is therefore expected to be a function of his/her propensity to trust when there are no experiential elements to factor in.…”
Section: Trust In Mobile Banking Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, e-commerce systems should be well designed or be made to imply the sellers are trustable, even if the regardless of seller's actual trustworthiness is not high. Many researchers have intensively studied the structure and formation mechanisms of trust from the aspects of both individual and organizational, and have identified five types antecedents to consumer trust, including institution-based, personality-based and calculation-based sources for trust building [27][28][29][30].…”
Section: Trustmentioning
confidence: 99%